Defect passivation using a phosphonic acid surface modifier for efficient RP perovskite blue-light-emitting diodes - Mishra, Jayanta Kumar (2022)
Defect management strategies are vital for enhancing the performance of perovskite-based optoelectronic devices, such as perovskite-based light-emitting diodes (PeLEDs). As additives can fucntion both as acrystallization modifier and/or defect passivator, a thorough study on the roles of additives is essential, especially for blue emissive Pe-LEDs, where the emission is strictly controlled by the n-domain distribution of the Ruddlesden–Popper (RP, L2An–1PbnX3n+1, where L refers to a bulky cation, while A and X are monovalent cation, and halide anion, respectively) perovskite films. Of the various additives that are available, octyl phosphonic acid (OPA) is of immense interest because of its ability to bind with uncoordinated Pb2+ ( notorious for nonradiative recombination) and therefore passivates them. Here, with the help of various spectroscopic techniques, such as X-ray photon-spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), and photoluminescence quantum yield (PLQY) measurements, we demonstrate the capability of OPA to bind and passivate unpaired Pb2+ defect sites. Modification to crystallization promoting higher n-domain formation is also observed from steady-state and transient absorption (TA) measurements. With OPA treatment, both the PLQY and EQE of the corresponding PeLED showed improvements up to 53% and 3.7% at peak emission wavelength of 485 nm, respectively.